What I have is what I am: Differences in demographics, suicidal thoughts and behaviors, and firearm behavior and beliefs between firearm owners who do and do not primarily identify as firearm owners. (September 2019) - Anestis, Michael D.; Houtsma, Claire
Abstract: Non-legislative forms of means safety (i.e., safe firearm storage practices) have been promoted as a way to reduce elevated suicide risk found among firearm owners. However, evidence suggests that some firearm owners are less willing than others to engage in these practices. The current study aimed to understand factors that differentiate firearm owners' beliefs and behaviors that are relevant to suicide risk by examining differences between individuals for whom firearm ownership represents a central aspect of identity (i.e., primary firearm owners) versus firearm owners who primarily identify with some other demographic or occupational characteristic. Results of main analyses revealed that primary firearm owners were more likely to be male, were less likely to have experienced suicidal ideation, were less likely to store their firearms safely across a number of storage methods, and were less open to means safety across all storage methods. These findings highlight demographically which firearm owners may be more likely to view firearm ownership as central to their identity and also suggest that this identification may be associated with beliefs and behaviors that increase suicide risk. Future firearm suicide prevention efforts should focus on culturally competent discussions and messaging to find common ground with firearm owners and to increase the salience of suicide among firearm owners.